SAE Technical Paper Series 2016
DOI: 10.4271/2016-01-0841
|View full text |Cite
|
Sign up to set email alerts
|

An Optical Characterization of the Effect of High-Pressure Hydrodynamic Cavitation on Diesel

Abstract: Most modern high-pressure common rail diesel fuel injection systems employ an internal pressure equalization system in order to provide the force necessary to support needle lift, enabling precise control of the injected fuel mass. This results in the return of a substantial proportion of the high-pressure diesel back to the fuel tank. The diesel fuel flow occurring in the injector spill passages is expected to be a cavitating flow, which is known to promote fuel ageing. The cavitation of diesel promotes nano-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The recirculation of high-pressure fuel across control valve nozzles is capable of stressing the fuel, which may lead to premature ageing and degradation. 3035 Four types of deposits have been observed to form throughout the fuel injection system in these studies. They are (1) a hard lacquer coating the internal stainless steel surfaces, (2) sticky brown/black deposits (likely to be caused by fuel ageing and degradation), (3) crusty brown/black carbonaceous aggregates that collect in small clearance regions and (4) black particles and aggregates with a ferromagnetic response.…”
Section: Introductionmentioning
confidence: 95%
“…The recirculation of high-pressure fuel across control valve nozzles is capable of stressing the fuel, which may lead to premature ageing and degradation. 3035 Four types of deposits have been observed to form throughout the fuel injection system in these studies. They are (1) a hard lacquer coating the internal stainless steel surfaces, (2) sticky brown/black deposits (likely to be caused by fuel ageing and degradation), (3) crusty brown/black carbonaceous aggregates that collect in small clearance regions and (4) black particles and aggregates with a ferromagnetic response.…”
Section: Introductionmentioning
confidence: 95%
“…1618 A further industry study of the effect of ultrasonic cavitation on diesel fuel showed that the ultrasonic excitation produced sono-chemical pyrolysis reactions that led to the formation of sticky black gums and soot-like nano-particles and aggregated particulates. 13 In parallel with this, Jeshani, 19 Fatmi 20 and Lockett et al 12,21,22 have investigated the effect of hydrodynamic cavitation in diesel nozzles on diesel fuel. This work employed time-resolved in situ measurements of the optical attenuation coefficient of various diesel fuel samples as a function of cavitation exposure time, together with 2-column gas chromatography (2-D GC×GC) measurements of the composition of samples obtained before and after cavitation, and ultraviolet-visible (uv-vis) absorption spectrophotometry.…”
Section: Introductionmentioning
confidence: 97%